DEVELOPMENT OF THE INDONESIAN SUICIDAL BEHAVIOR SCALE - Nurcahyo, Firmanto Adi; Valentina, Tience Debora (Psychological thought, 2025)
Suicide is a mental health phenomenon throughout the world. Measuring suicidal behavior requires instruments with strong psychometric properties. There are limitations to the scale of suicidal behavior for the Indonesian context. Therefore, this research was conducted to develop the Indonesian Suicidal Behavior Scale (ISBS), a valid and reliable scale to measure the suicidal behavior of Indonesian adults. The development of the scale uses 3 dimensions of suicidal behavior, namely depression, hopelessness, and the capability to attempt suicide. 27 items were developed based on these three dimensions. A total of 764 respondents participated in this study. Evidence of internal structure validity, as conducted by confirmatory factor analysis, confirmed three factors that fit the data. Evidence of the association's validity was supported by the correlation between the ISBS score and the PHQ-9. Cronbach’s Alpha reliability for the three dimensions ranged from  .897- .944. Based on the results of this study, the ISBS can be considered a valid instrument for measuring suicidal behavior tendencies for Indonesian adults.